The Laws on Witchcraft in Brunei and Malaysia: An Analysis Based on Maqasid Al-Shariah - Mohd Zawawi, Mohamad Ridhuan (IJoIS: Indonesian Journal of Islamic Studies, 2025)
The practice of witchcraft in society has existed for thousands of years and has been passed down through generations. The best approach to preventing acts of witchcraft is through legislation. Brunei and Malaysia are among the countries that codify witchcraft as a crime under Sharia Law through the Brunei Penal Code Order 2013, the Kelantan Syariah Penal Code Enactment (I) 2019 and the Terengganu Syariah Criminal Offenses (Takzir) (Amendment) Enactment 2022. The codified witchcraft laws in both countries represent a contemporary ijtihad by leaders and legal experts who recognize the necessity of legislating such provisions. However, the concept of punishment for practitioners of witchcraft in these countries does not fully align with Islamic legal principles. This raises the question do the codified witchcraft laws in Brunei and Malaysia align with Maqasid al-Shariah? Therefore, the objective of this study is to analyze the witchcraft laws in Brunei and Malaysia from the perspective of Maqasid al- Shariah. This study adopts a qualitative approach, utilizing document and content analysis as its data collection methods. The findings reveal that the witchcraft laws in Brunei and Malaysia align with Maqasid al-Shariah as they fulfill the aspects of preserving religion, life, intellect, wealth and lineage.